Controlled n-Doping of Naphthalene Diimide-Based Two-Dimensional Polymers - Evans, Austin M.; Collins, Kelsey A.; Xun, Sangni; Allen, Taylor G.; Jhulki, Samik; Castano, Ioannina; Smith, Hannah L; Strauss, Michael J.; Oanta, Alexander; Liu, Lujia; Sun, Lei; Reid, Obadiah G.; et al. (Advanced Materials, 2022)
2D polymers (2DPs) are promising as structurally well-defined, permanently porous, organic semiconductors. However, 2DPs are nearly always isolated as closed shell organic species with limited charge carriers, which leads to low bulk conductivities. Here, the bulk conductivity of two naphthalene diimide (NDI)-containing 2DP semiconductors is enhanced by controllably n-doping the NDI units using cobaltocene (CoCp2). Optical and transient microwave spectroscopy reveal that both as-prepared NDI-containing 2DPs are semiconducting with sub-2 eV optical bandgaps and photoexcited charge-carrier lifetimes of tens of nanoseconds. Following reduction with CoCp2, both 2DPs largely retain their periodic structures and exhibit optical and electron-spin resonance spectroscopic features consistent with the presence of NDI-radical anions. While the native NDI-based 2DPs are electronically insulating, maximum bulk conductivities of >10−4 S cm−1 are achieved by substoichiometric levels of n-doping. Density functional theory calculations show that the strongest electronic couplings in these 2DPs exist in the out-of-plane (π-stacking) crystallographic directions, which indicates that cross-plane electronic transport through NDI stacks is primarily responsible for the observed electronic conductivity. Taken together, the controlled molecular doping is a useful approach to access structurally well-defined, paramagnetic, 2DP n-type semiconductors with measurable bulk electronic conductivities of interest for electronic or spintronic devices.</

Coronene Derivatives for Transparent Organic Photovoltaics Through Inverse Materials Design - Sorli, Jeni C.; Friederich, Pascal; Sanchez-Lengeling, Benjamin; Davy, Nicholas C.; Ndjawa, Guy Olivier Ngongang; Smith, Hannah L; Lin, Xin; Lopez, Stephen A.; Ball, Melissa L.; Kahn, Antoine; Aspuru-Guzik, Alan; Loo, Yueh-Lin (Journal of Materials Chemistry C, 2020)
To accelerate materials discovery, computational methods such as inverse materials design have been proposed to predict the properties of target compounds of interest for specific applications. This in silico process can be used to guide subsequent synthesis and characterization. Inverse design is especially relevant for the field of organic molecules, for which there are nearly infinite synthetic modifications possible. With a target application of UV-absorbing, visibly transparent solar cells in mind, we calculated the orbital and transition energies of over 360 possible coronene derivatives. Our screening, or the constraints we imposed on the calculated series, resulted in the selection of three new derivatives, namely contorted pentabenzocoronene (cPBC), contorted tetrabenzocoronene (cTBC), and contorted tetrabenzofuranylbenzocoronene (cTBFBC) for synthesis and characterization. Our materials characterization found agreement between our calculated and experimental energy values, and through testing of these materials in organic photovoltaic (OPV) devices, we fabricated solar cells with an open-circuit voltage of 1.84 V and an average visible transparency of 88% of the active layer; both quantities exceed previous records for visibly transparent coronene-based solar cells. This work highlights the promise of inverse materials design for future materials discovery, as well as improvements to an exciting application of UV-targeted solar cells.</

Design of UV Absorbing Donor Molecules for Nearly Imperceptible Organic Solar Cells - Ball, Melissa L.; Burlingame, Quinn; Smith, Hannah L; Liu, Tianran; Parkin, Sean R.; Kahn, Antoine; Loo, Yueh-Lin (ACS Energy Letters, 2022)
Transparent photovoltaic cells are an emerging technology that can provide point-of-use electricity generation for building integrated applications. While most transparent solar cells to date target absorption of the photon-rich near-infrared portion of the solar spectrum, these devices compromise color neutrality and transparency because of parasitic absorption of long-wavelength visible light. One solution to eliminate parasitic absorption is to employ materials that absorb near-ultraviolet light with sharper absorption cutoffs. Herein, we demonstrate organic donor materials based on N,N′-diaryl-diamines that incorporate a series of aryl linkers to systematically tune their absorption profiles. When paired with acceptor 4,6-bis(3,5-di-4-pyridinylphenyl)-2-methylpyrimidine in an inverted architecture with an indium tin oxide top electrode and an organic optical outcoupling layer, the three best-performing transparent solar cells exhibit average photopic-response-weighted transmittances of 80.3−82.0% and color-rendering indices of 95.0−97.1, both of which are records for organic photovoltaics, with power-conversion efficiencies of 0.43−0.70%.</

Molecular Dopants: Tools to Control the Electronic Structure of Metal Halide Perovskite Interfaces - Zhang, Fengyu; Smith, Hannah L; Kahn, Antoine (Applied Physics Reviews, 2021)
In the standard configurations of metal halide perovskite solar cell, the active layer, or absorber, follows a p-i-n or n-i-p electronic structure that is designed to enhance the separation and extraction of photo-induced charge carriers. The control of the Fermi level position across the film, between electron and hole transport layers, is therefore of paramount importance. Direct localized doping in metal halide perovskites being still elusive, the design of n-i-p and p-i-n structures has so far relied predominantly on surface and interface doping of the perovskite as well as on the control of the work function of the substrate and transport layers on which, or between which, the absorber is being placed. We provide here a short review of that work, emphasizing the fundamental studies of electronic structure performed on systems modified with organic molecular dopants. The review starts with a justification for the effectiveness of interface doping, based on the ability to move the Fermi level across the gap of the perovskite. We then review work done on the deposition of molecular oxidants and reductants on perovskite surfaces, including the mitigation of the surface states, and the impact of these dopants on energy level alignment with substrate and charge transport layers. The second part of the review focuses on the use of molecular dopants to either modify the work function of electron or hole transport layers to establish the boundary conditions for a p-i-n or n-i-p structure, or to enhance the conductivity of these layers in order to facilitate charge carrier extraction. Final considerations are also given on recent work on bulk doping of the perovskite layer with molecular dopants.</

n-Doping of a Low-Electron-Affinity Polymer Used as an Electron-Transport Layer in Organic Light-Emitting Diodes - Smith, Hannah L; Dull, Jordan T.; Longhi, Elena; Barlow, Stephen; Rand, Barry P.; Marder, Seth R.; Kahn, Antoine (Advanced Functional Materials, 2020)
n-Doping electron-transport layers (ETLs) increases their conductivity and improves electron injection into organic light-emitting diodes (OLEDs). Because of the low electron affinity and large bandgaps of ETLs used in green and blue OLEDs, n-doping has been notoriously more difficult for these materials. In this work, n-doping of the polymer poly[(9,9-dioctylfluorene-2,7-diyl)-alt-(benzo[2,1,3]thiadiazol-4,7-diyl)] (F8BT) is demonstrated via solution processing, using the air-stable n-dopant (pentamethylcyclopentadienyl) (1,3,5-trimethylbenzene)ruthenium dimer [RuCp*Mes]2. Undoped and doped F8BT films are characterized using ultraviolet and inverse photoelectron spectroscopy. The ionization energy and electron affinity of the undoped F8BT are found to be 5.8 and 2.8 eV, respectively. Upon doping F8BT with [RuCp*Mes]2, the Fermi level shifts to within 0.25 eV of the F8BT lowest unoccupied molecular orbital, which is indicative of n-doping. Conductivity measurements reveal a four orders of magnitude increase in the conductivity upon doping and irradiation with ultraviolet light. The [RuCp*Mes]2-doped F8BT films are incorporated as an ETL into phosphorescent green OLEDs, and the luminance is improved by three orders of magnitude when compared to identical devices with an undoped F8BT ETL.</
Keywords: electron-transport layers; low-electron-affinity polymers n-doping; organic light-emitting diodes; organic semiconductors

Powerful Organic Molecular Oxidants and Reductants Enable Ambipolar Injection in a Large-Gap Organic Homojunction Diode - Smith, Hannah L; Dull, Jordan T.; Mohapatra, Swagat K.; Kurdi, Khaled Al; Barlow, Stephen; Marder, Seth R.; Rand, Barry P.; Kahn, Antoine (ACS Applied Materials and Interfaces, 2022)
Doping has proven to be a critical tool for enhancing the performance of organic semiconductors in devices like organic light-emitting diodes. However, the challenge in working with high ionization- energy (IE) organic semiconductors is to find p-dopants with correspondingly high electron affinity (EA) that will improve the conductivity and charge carrier transport in a film. Here, we use an oxidant that has been recently recognized to be a very strong p-type dopant, hexacyano-1,2,3-trimethylene-cyclopropane (CN6-CP). The EA of CN6-CP has been previously estimated via cyclic voltammetry to be 5.87 eV, almost 300 meV higher than other known high-EA organic molecular oxidants. We measure the frontier orbitals of CN6-CP using ultraviolet and inverse photoemission spectroscopy techniques and confirm a high EA value of 5.88 eV in the condensed phase. The introduction of CN6-CP in a film of large-band-gap, large-IE phenyldi(pyren-1-yl)phosphine oxide (POPy2) leads to a significant shift of the Fermi level toward the highest occupied molecular orbital and a 2 orders of magnitude increase in conductivity. Using CN6-CP and n-dopant (pentamethylcyclopentadienyl)(1,3,5-trimethylbenzene)ruthenium (RuCp*Mes)2, we fabricate a POPy2-based rectifying p−i−n homojunction diode with a 2.9 V built-in potential. Blue light emission is achieved under forward bias. This effect demonstrates the dopant- enabled hole injection from the CN6-CP-doped layer and electron injection from the (RuCp*Mes)2-doped layer in the diode.
Keywords: organic semiconductors; p-dopants; n-dopants; photoemission spectroscopy; p−i−n homojunctions; light emission

Sensitization of Silicon by Singlet Exciton Fission in Tetracene - Einzinger, Markus; Wu, Tony; Kompalla, Julia; Smith, Hannah L; Perkinson, Colin F.; Nienhaus, Lea; Wieghold, Sarah; Congreve, Daniel N.; Kahn, Antoine; Bawend, Moungi G.; Baldo, Marc A. (Nature, 2019)
Silicon dominates contemporary solar cell technologies. But when absorbing photons, silicon (like other semiconductors) wastes energy in excess of its bandgap. Reducing these thermalization losses and enabling better sensitivity to light is possible by sensitizing the silicon solar cell using singlet exciton fission, in which two excited states with triplet spin character (triplet excitons) are generated from a photoexcited state of higher energy with singlet spin character (a singlet exciton). Singlet exciton fission in the molecular semiconductor tetracene is known to generate triplet excitons that are energetically matched to the silicon bandgap. When the triplet excitons are transferred to silicon they create additional electron–hole pairs, promising to increase cell efficiencies from the single-junction limit of 29 per cent to as high as 35 per cent. Here we reduce the thickness of the protective hafnium oxynitride layer at the surface of a silicon solar cell to just eight angstroms, using electric-field-effect passivation to enable the efficient energy transfer of the triplet excitons formed in the tetracene. The maximum combined yield of the fission in tetracene and the energy transfer to silicon is around 133 per cent, establishing the potential of singlet exciton fission to increase the efficiencies of silicon solar cells and reduce the cost of the energy that they generate.</

Solution-Processed Organic and Halide Perovskite Transistors on Hydrophobic Surfaces - Ward, Jeremy W.; Smith, Hannah L; Zeidell, Andrew; Diemer, Peter J.; Baker, Stephen R.; Lee, Hyunsu; Payne, Marcia M.; Anthony, John E.; Guthold, Martin; Jurchescu, Oana D. (ACS Applied Materials and Interfaces, 2017)
Solution-processable electronic devices are highly desirable due to their low cost and compatibility with flexible substrates. However, they are often challenging to fabricate due to the hydrophobic nature of the surfaces of the constituent layers. Here, we use a protein solution to modify the surface properties and to improve the wettability of the fluoropolymer dielectric Cytop. The engineered hydrophilic surface is successfully incorporated in bottom-gate solution-deposited organic field-effect transistors (OFETs) and hybrid organic–inorganic trihalide perovskite field-effect transistors (HTP-FETs) fabricated on flexible substrates. Our analysis of the density of trapping states at the semiconductor–dielectric interface suggests that the increase in the trap density as a result of the chemical treatment is minimal. As a result, the devices exhibit good charge carrier mobilities, near-zero threshold voltages, and low electrical hysteresi
Keywords: organic thin-film transistors; flexible electronics; organic semiconductors; halide perovskites; charge carrier mobility